Differences in Morphologic and Hemodynamic Characteristics for “PHASES-Based” Intracranial Aneurysm Locations - Varble, N.; Rajabzadeh-Oghaz, H.; Wang, J.; Siddiqui, A.; Meng, H.; Mowla, A. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Several recent prospective studies have found that unruptured intracranial aneurysms at various anatomic locations have different propensities for future rupture. This study aims to uncover the lack of understanding regarding rupture-prone characteristics, such as morphology and hemodynamic factors, associated with different intracranial aneurysm location.MATERIALS AND METHODS: We investigated the characteristics of 311 unruptured aneurysms at our center. Based on the PHASES study, we separated and compared morphologic and hemodynamic characteristics among 3 aneurysm location groups: 1) internal carotid artery; 2) middle cerebral artery; and 3) anterior communicating, posterior communicating, and posterior circulation arteries.RESULTS: A mixed model statistical analysis showed that size ratio, low wall shear stress area, and pressure loss coefficient were different between the intracranial aneurysm location groups. In addition, a pair-wise comparison showed that ICA aneurysms had lower size ratios, lower wall shear stress areas, and lower pressure loss coefficients compared with MCA aneurysms and compared with the group of anterior communicating, posterior communicating, and posterior circulation aneurysms. There were no statistical differences between MCA aneurysms and the group of anterior communicating, posterior communicating, and posterior circulation aneurysms for morphologic or hemodynamic characteristics.CONCLUSIONS: ICA aneurysms may be subjected to less rupture-prone morphologic and hemodynamic characteristics compared with other locations, which could explain the decreased rupture propensity of intracranial aneurysms at this location.AcomAanterior communicating arteryIAintracranial aneurysmLSAlow wall shear stress areaPcomAposterior communicating arteryPHASESPopulation, Hypertension, Age, Size of aneurysm, Earlier SAH from another aneurysm, and Site of aneurysmPLcpressure loss coefficientSRsize ratioWSSwall shear stress